Simulating land use change for sustainability: a case study of the northern slope of Tianshan Mountains - Xiang Qiao; Hongguang Liu; Zhixin Hao; Ping Gong; Yang Liu; Changkun Yang; Pengfei Li (International Journal of Digital Earth)
The north slope of the Tianshan Mountains (NSTM), an arid region in northwest China, faces challenges including human-land conflicts, water imbalances, and ecological fragility. As a key urban cluster in the nation's sustainable development plan, understanding land use change and future trends is crucial for effective planning. However, the complexity of land use systems and the limitations of existing models in capturing temporal and spatial dynamics pose challenges. Therefore, this study integrates the System Dynamics (SD) and Patch-generating Land Use Simulation (PLUS) models to analyze historical and projected land use change on the NSTM and proposes targeted management strategies focused on food security and ecological protection. Results indicate that from 2000 to 2020, land use changes primarily involved interconversion among cultivated land, grassland, and unused land, with varying intensities. The integrated SD and PLUS model simulated future land use trends with 98.84% accuracy and a Kappa Coefficient of 0.98. Under all scenarios (SSP119, SSP245, and SSP585), ecological land areas were primarily converted to cultivated land, whereas construction land expanded into adjacent cultivated areas. Based on the spatial patterns of major land use change, we propose targeted management measures for key areas to support sustainable ecological practices in arid regions.